N Nilai SPF (Sun Protection Factor) Dan Evaluasi Fisik Sediaan Hair Conditioner Ekstrak Etanol Bunga Rosella (Hibiscus Sabdariffa L.) Sebagai Sun Protection - Bila, Widi Salsa; Audina, Mia; Rahmadani, Rahmadani; Malahayati, Siti (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Hair is a characteristic appearance. Hair and scalp problems can occur due to exposure to sunlight in the form of ultraviolet (UV) rays. Hair conditioner made from natural ingredients which are rich in antioxidants can solve problems and protect hair from sun exposure. Rosella is one of the plants rich in anthocyanins as antioxidants which can stimulate hair growth by relaxing the muscles in the blood vessels in the hair follicles which facilitate a constant supply of blood with nutrients to the hair follicle cells. Objective: Observing and analyzing the effect of roselle flower ethanol extract with a concentration of 5%, 10%, 15% in hair conditioner preparations as sun protection on the evaluation of SPF (Sun Protection Factor) and physicochemical evaluations. Methods: This study used a one shot case study design. Hair conditioners are formulated with different concentrations of the active substance ethanol extract of rosella flowers, namely 5%, 10% and 15%. The evaluation included organoleptic, homogeneity, pH, viscosity, cream type and in vitro SPF activity test. Data were analyzed using one way ANOVA. Results: The results of the study showed that the variation of the active substance affected the differences in the results of the physical evaluation on the pH and viscosity test, as well as the SPF activity test. Based on the statistical results of one way ANOVA, the results obtained were <0.05, meaning that there was an effect of variations in the concentration of the active substance of the ethanol extract of rosella flowers on testing pH, viscosity and SPF activity on hair conditioner preparations. Conclusion: The results of the activity testing and phsycochemical  Evaluation in rosella flowers extraxt hair conditioner formulation showed significant differences in the results from the effect of variations in the active substance.